1986
DOI: 10.1007/bf02294063
|View full text |Cite
|
Sign up to set email alerts
|

Tests for equality of several alpha coefficients when their sample estimates are dependent

Abstract: coefficient alpha, test reliability, internal consistency, hypothesis testing, repeated measures,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Thus, these results help to validate the use of these scales across a wide range of sample diversity. However, comparable omnibus (Woodruff & Feldt, 1986) and pairwise comparisons (Abd-El-Fattah & Hassan, 2011)ofthese alpha coefficients suggested that the 12-item QSI-satisfaction subscale offered higher levels of internal consistency than the existing satisfaction scales in 18 of the 19 subgroups examined. Similarly, even the 6-item QSI-satisfaction subscale offered higher internal consistency than the existing satisfaction scales in 13 of the 19 subgroups, despite being markedly shorter in length.…”
Section: Generalizability Of Internal Consistenciesmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, these results help to validate the use of these scales across a wide range of sample diversity. However, comparable omnibus (Woodruff & Feldt, 1986) and pairwise comparisons (Abd-El-Fattah & Hassan, 2011)ofthese alpha coefficients suggested that the 12-item QSI-satisfaction subscale offered higher levels of internal consistency than the existing satisfaction scales in 18 of the 19 subgroups examined. Similarly, even the 6-item QSI-satisfaction subscale offered higher internal consistency than the existing satisfaction scales in 13 of the 19 subgroups, despite being markedly shorter in length.…”
Section: Generalizability Of Internal Consistenciesmentioning
confidence: 90%
“…As seen in Table 3, analyses in the 696 respondents providing 2-month follow-up data in the current project provided similar results. An omnibus test (Woodruff & Feldt, 1986) for differences across the six test-retest correlations of the satisfaction scales revealed a significant difference, v 2 (5) = 111.5, p\.0001, and subsequent pairwise comparisons (Abd-El-Fattah & Hassan, 2011) revealed that the 12-item QSI-satisfaction subscale had higher levels of test-retest reliability than the existing scales, despite being much shorter in length. Similar analyses in the 419 respondents reporting little to no change in their sexual satisfaction over time yielded stronger test-retest correlations for all of the scales (the follow-up survey did not include comparable questions about change in sexual dissatisfaction, and so it was not possible to calculate similar statistics for the QSI-dissatisfaction scales).…”
Section: Test-retest Reliabilitiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Little further increase in reliability was found above seven response categories: alpha coefficients for scales with 7, 8, 9, 10, 11, and 101 response categories were all very similar. Using Feldt's test for the significance of differences between more than two related alpha coefficients (Woodruff & Feldt, 1986), it was determined that none of the differences between the alpha coefficients were statistically significant: using either of the recommended statistics HAN2 or UX1, χ 2 (10) < 18.31, p > .05.…”
Section: Reliabilitymentioning
confidence: 99%
“…Comparisons of ethnic differences in the reliability coefficients of derived variables were performed using Feldt's W statistic (data not shown). 66 Differences between racial/ethnic groups on quality-ofcare, and all patient-reported measures were tested with separate linear regression models for continuous variables and logistic regression models for categorical variables declaring non-Hispanic white patients as the reference group. To account for multiple comparisons, group differences with p values≤0.001 were reported as statistically significant.…”
Section: Discussionmentioning
confidence: 99%